Subjective cognitive decline may mediate the occurrence of postoperative delirium by P-tau undergoing total hip replacement: The PNDABLE study - Liu, Fanghao; Lin, Xu; Lin, Yanan; Deng, Xiyuan; Dong, Rui; Wang, Bin; Bi, Yanlin (Frontiers in Aging Neuroscience, 2022)
Objective:We again investigated the relationship between subjective cognitive decline(SCD)and postoperative delirium(POD)with a larger sample queue.We also determined whether SCD could cause the occurrence of POD through cerebrospinal fluid(CSF)biomarkers.Methods:A prospective,observational cohort study was implemented in the Qingdao Municipal Hospital Affiliated with Qingdao University.This study recruited 1471 qualified patients affiliated with the Perioperative Neurocognitive Disorder And Biomarker Lifestyle(PNDABLE)study scheduled for total hip replacement under combined spinal and epidural anesthesia from June 2020 to May 2022.The Mini-Mental State Examination(MMSE)and the Montreal Cognitive Assessment(MoCA)were used to assess the cognitive level of the patients the day before surgery.Pittsburgh sleeps quality index(PSQI)scale was used to assess sleep status.Patients were divided into the SCD group and the non-SCD(NSCD)group based on the Subjective Cognitive Decline Scale(SCDS).CSF was collected after a successful spinal-epidural combined puncture,and amyloid-β40(Aβ40),amyloid-β42(Aβ42),total tau(T-tau),and phosphorylated tau(P-Tau) in CSF were analyzed by enzyme-linked immunosorbent assays.After the surgery,the incidence of POD was determined by the Confusion Assessment Scale(CAM),and Memorial Delirium Assessment Scale(MDAS) score was used to determine the severity of POD.Logistic regression and sensitivity analysis were performed to determine the relationship between CSF biomarkers,SCD,and POD.The mediating effect was used to analyze the function of specific CSF biomarkers in the relationship between SCD and POD.The risk factors of SCD were also separately verified by logistic regression and sensitivity analysis models.Results:The total incidence rate of POD was 19.60%(n=225/1148),which was 29.3%(n=120/409)in the SCD group and 14.2%(n=105/739) in the NSCD group.We comprehensively considered the effect of covariates such as age, hypertension, and diabetes.Multivariate logistic regression analysis showed that SCD(OR=1.467,95%CI:1.015–2.120,P=0.042) and P-tau(OR=1.046, 95%CI:1.028–1.063,P<0.001) were risk factors for POD.The sensitivity analysis results were consistent with the above results.Mediation analysis showed that the relationship between SCD and POD was partially mediated by P-tau,which accounted for 31.25%(P-tau,IE=4.279 × 10−2,P<0.001). For SCD,the results of logistic regression analysis models showed that age(OR=1.035,95% CI:1.020–1.049,P<0.001),higher preoperative PSQI score(OR=1.047,95%CI: 1.014–1.080,P=0.005),and P-tau(OR=1.015, 95%CI:1.002–1.028,P=0.021) were risk factors for SCD,and subsequent sensitivity analysis confirmed this result after adjustment for ASA grade,height,and weight.Conclusion:Patients with SCD are more likely to develop POD undergoing total hip replacement,and SCD can mediate the occurrence of POD via P-tau.Clinical Trial Registration:This study was registered at China Clinical Trial Registry (Chictr2000033439).